Role of Cardiovascular Magnetic Resonance in Native Valvular Regurgitation: A Comprehensive Review of Protocols, Grading of Severity, and Prediction of Valve Surgery - Vermes, Emmanuelle; Iacuzio, Laura; Levy, Franck; Bohbot, Yohann; Renard, Cédric; Gerber, Bernhard; Maréchaux, Sylvestre; Tribouilloy, Christophe (Frontiers in Cardiovascular Medicine, 2022)
Valvular regurgitation is common in developed countries with an increasing prevalence due to the aging of the population and more accurate diagnostic imaging methods. Echocardiography is the gold standard method for the assessment of the severity of valvular heart regurgitation. Nonetheless, cardiovascular magnetic resonance (CMR) has emerged as an additional tool for assessing mainly the severity of aortic and mitral valve regurgitation in the setting of indeterminate findings by echocardiography. Moreover, CMR is a valuable imaging modality to assess ventricular volume and flow, which are useful in the calculation of regurgitant volume and regurgitant fraction of mitral valve regurgitation, aortic valve regurgitation, tricuspid valve regurgitation, and pulmonary valve regurgitation. Notwithstanding this, reference values and optimal thresholds to determine the severity and prognosis of valvular heart regurgitation have been studied lesser by CMR than by echocardiography. Hence, further larger studies are warranted to validate the potential prognostic relevance of the severity of valvular heart regurgitation determined by CMR. The present review describes, analyzes, and discusses the use of CMR to determine the severity of valvular heart regurgitation in clinical practice.